2015
DOI: 10.1021/acs.jpclett.5b02419
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Electron Spin Polarization in Water Splitting

Abstract: We show that in an electrochemical cell, in which the photoanode is coated with chiral molecules, the overpotential required for hydrogen production drops remarkably, as compared with cells containing achiral molecules. The hydrogen evolution efficiency is studied comparing seven different organic molecules, three chiral and four achiral. We propose that the spin specificity of electrons transferred through chiral molecules is the origin of a more efficient oxidation process in which oxygen is formed in its tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 45 publications
8
192
0
Order By: Relevance
“…Altogether, the results reported in ref. are well consistent with chiral molecules being good spin filters reported by others.…”
Section: Water Splitting Using Chiral Moleculessupporting
confidence: 92%
See 2 more Smart Citations
“…Altogether, the results reported in ref. are well consistent with chiral molecules being good spin filters reported by others.…”
Section: Water Splitting Using Chiral Moleculessupporting
confidence: 92%
“…Beyond the effect on the onset in the water-splitting process, the amount of evolved hydrogen has been collected and quantified. [35] The amount of evolved hydrogen as a function of time has been compared with chiral organic linkers ( Figure 12A) and achiral molecules ( Figure 12B). It can be observed that the amount of hydrogen collected when chiral molecules are employed is significantly larger than that which is obtained with achiral ones, keeping other conditions identical.…”
Section: Tio 2 Functionalized With Chiral Versus Achiral Molecules Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Although spin is rarely discussed in works exploring artificial photosynthesis, recent theoretical studies suggest that the overpotential required to split water is linked to restrictions on the electrons’ spin in generating a ground state triplet oxygen molecule ,. In a recent experimental work, it has been shown that when the anode in the water‐splitting cell is coated with chiral molecules, the overpotential is reduced …”
Section: The Ciss Effectmentioning
confidence: 99%
“…[8] Recently a possible solution to this problem was proposed by Ron Naaman and was demonstrated in collaboration with our group. [12,13] The functionalization of TiO 2 anodes with chiral supramolecular polymers that are able to act as spin filters -through an effect called chiral induced spin selectivity (CISS) [14] -demonstrated the possibility of simultaneously reducing the production of H 2 O 2 and increasing the current.…”
Section: Introductionmentioning
confidence: 99%